BUILDINGS’ DAMAGE AT HOREMI VILLAGE, ARKADIA, GREECE: EVALUATION OF THE GEOTECHNICAL CONDITIONS AT SHALLOW DEPTHS - Kynigalaki M., Kynigalaki M.; Kanaris, D.; Nikolaou, N.; Kontogianni, V. (Bulletin of the Geological Society of Greece, 2010)
Horemi village is located in Central Peloponnesus, at the western margins of Megalopoli basin. For several years failure phenomena on the village buildings have been reported, causing problems related both to the safety of the inhabitants, as well as to the development of the area. For the above reasons a geotechnical investigation program was carried out, to study the origin of the failures and lead to certain conclusions for the mitigation of the phenomena. In situ exploratory works, with reference to the investigation of litho-stratigraphy, ground foundation conditions, as well as laboratory testing, provided the necessary data for further research testing of the soil physical and mechanical parameters. Building failure recording, trial pits description, sample collection and laboratory testing, pointed out that failure phenomena are due to geotechnical rather than geological effects. The detection of a clayey horizon, presenting high to very high plasticity and swelling behavior, related to the significant montmorillonite proportion in the surface or shallow geological formations, showed good correlation to building damages. The aforementioned observations are considered to clarify the case presented in this paper.